2022
DOI: 10.1111/jep.13764
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID‐19 vaccine uptake among healthcare professionals and the general population in Cyprus: A web‐based cross‐sectional survey

Abstract: Objective This study aims to examine the factors influencing COVID‐19 vaccine uptake among healthcare professionals (HCPs) and the general population in Cyprus. Methods A web‐based cross‐sectional study was conducted (November 2021–January 2022), using a self‐administered, anonymous questionnaire to collect information covering a wide range of potential determinants including sociodemographic and health‐related characteristics, trust in the healthcare system, satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This figure is consistent with a study conducted in Cyprus, where the vaccination rate was reported at 70.5%. 33 However, it exceeds the rates found in Ethiopian studies 31 at 62.1%, while falling below rates observed in Egypt 34 at 90%, the USA 35 at 81% and Greece 36 at 77.3%. The observed variation in vaccination rates across these regions may be attributed to several factors, including differences in awareness campaigns, cultural beliefs, healthcare infrastructure, vaccine availability and governmental policies promoting vaccination.…”
Section: Bmj Public Healthmentioning
confidence: 67%
“…This figure is consistent with a study conducted in Cyprus, where the vaccination rate was reported at 70.5%. 33 However, it exceeds the rates found in Ethiopian studies 31 at 62.1%, while falling below rates observed in Egypt 34 at 90%, the USA 35 at 81% and Greece 36 at 77.3%. The observed variation in vaccination rates across these regions may be attributed to several factors, including differences in awareness campaigns, cultural beliefs, healthcare infrastructure, vaccine availability and governmental policies promoting vaccination.…”
Section: Bmj Public Healthmentioning
confidence: 67%
“…Similarly, the current research did not explore sociodemographic and psychological determinants which also influence vaccine decisiveness. A study with a large sample of participants, which was conducted a few months after our data collection (November 2021 and January 2022), showed the interplay of sociodemographic, behavioral, and psychological factors influencing vaccine hesitancy in the general population and healthcare professionals in Cyprus [88] (see also [89]). The determinants found to influence higher vaccination rates in the general population included age (with older individuals being more likely to be vaccinated), higher trust in national healthcare authorities' guidelines, and increased vaccination knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge will help individuals protect themselves from the virus and minimize the possibility of individuals' endorsement of conspiracy theories. For instance, a number of studies examining vaccine-related knowledge found that the better the understanding of vaccination, the more likely people are to choose to be vaccinated against the SARS-CoV-2 virus [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%